Shear Lag Effect and Its Additional Deflection Contribution of Composite Beam Bridges - Lu, Pengzhen; Qi, Zhenyi; Wu, Ying; Ding, Yu; Yang, Liu; Li, Yang (Periodica Polytechnica Civil Engineering, 2024)
The composite beam structure is widely used in the engineering field because it benefits from the advantages of two materials, presenting outstanding advantages for construction purposes. However, at present, there are issues with the analysis and solution of the composite beam structure, such as the difficulty in developing a suitable analytical theory and the low degree of refinement achieved by simulation analysis. To accurately grasp the mechanical behavior of the composite beam structure and achieve its refined analysis, this paper proposes a refined spatial grid element analysis method that can simultaneously obtain the internal forces, displacements, and stresses of various parts of a composite beam. Based on the above new method, the effects of geometrical structural factors such as wide-span ratio, high-span ratio, and web thickness with respect to the shear lag effect are analyzed. The distribution law of the shear lag coefficient and its additional deflection are analyzed. The results demonstrate that using this analysis method to calculate and analyze steel-concrete duplex type composite beams can directly obtain the internal forces and displacements of the joints of the composite beam roof, floor, and web. The spatial grid element analysis method provides both the theoretical and practical means to achieve both the overall and local refinement analysis of the composite beam structure.